Kentucky votes. U.S. house primary and general elections, 1920--1960 - Jewell, Malcolm E., 1928-2010 (University of Kentucky Press, 1963)
These three volumes of Kentucky election statistics at last make this basic tool of political research easily accessible to scholars, journalists, teachers, political candidates and others interested in primary and general election returns. In Kentucky, as in many other states, these figures have been available only in the Secretary of State's office, and there has been no compilation of percentages and pluralities necessary for comparative purposes. The source of all the statistics in these volumes is the official records in the office of the Secretary of State in Frankfort, Kentucky. All retu.